FIGURE 6. Botryllus flavus n in Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific) - Sanamyan, Karen; Sanamyan, Nadya (Zenodo, 2017)
FIGURE 6. Botryllus flavus n. sp., colonies. A, paratype KBPGI 1450/2; B, holotype KBPGI 1449/1; C and D, specimens from Kamchatka. Published as part of Sanamyan, Karen & Sanamyan, Nadya, 2017, Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific), pp. 301-321 in Zootaxa 4232 (3) on page 308, DOI:10.11646/zootaxa.4232.3.1, http://zenodo.org/record/293689